GROUNDWATER POLLUTION HAZARD ASSESSMENT IN YOGYAKARTA CITY, YOGYAKARTA SPECIAL PROVINCE, INDONESIA - , PISETH SENSAMRAS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Known as one of big cities in Indonesia, Yogyakarta City requires extensive groundwater resource since around 70% of whole populations are using shallow wells, so safe groundwater quality should be considered. The prediction of occurrence of groundwater pollution hazard is the beneficial key for sustainable groundwater quality management. This research has been conducted in term of three main objectives: determination of groundwater vulnerability, estimation of nitrate and organic chemical contaminant loading, and assessment of groundwater pollution hazard. Groundwater vulnerability is assessed by SVV method (Simple Vertical Vulnerability, Putra 2007). Nitrate and organic chemical contaminant loads are analyzed by stepwise processes (Johasson and Hirata, 2002